Long Bay - Limprecht, Eleanor (Melbourne : Sleepers, 2015)
In 1909 Rebecca Sinclair was sent to Long Bay Women's Reformatory after she was convicted of manslaughter. A mother-of-three had died at her house after a botched abortion. Rebecca was sentenced to three years hard labour, but less than six months into her prison term she gave birth to a child, a girl, who she kept with her in prison. Inspired by letters found in an archive and a photograph of a young woman prisoner, Long Bay is a compelling, moving novel that reveals the harsh realities of living in poverty - and falling in love.
Zweigstelle: Patientenbücherei Psychiatrie
Exemplar/Standort: Engl Limp (PatBü Psych)
Exemplar/Standort: Patientenbücherei Psychiatrie
Text in engl. Sprache
Keywords: Englisch; Fremdsprachiger Text; Historisches <20. Jahrhundert>; Frauen; Fiktionale Darstellung; Australien